PTAB mediated open air synthesis of sulfonamides, thiosulfonates and symmetrical disulfanes. Issue 24 (13th June 2018) - Sarkar, Debayan; Ghosh, Manoj Kumar; Rout, Nilendri
Graphical abstract: Highlights: The trio of sulfonamides, thiosulfonates and symmetric disulfanes is developed. Gram-scale synthesis of symmetric disulfanes and sulphonamides has been achieved. The methodology exhibits a metal-free and an open-air protocol. Abstract: A facile methodology has been described which has successfully simplified the generation of sulfonamides, thiosulfonates and symmetric disulfanes. This "trio" of reactions occur in an open air metal free atmosphere and has also been scaled up to grams making it suitable for commercialization. The reactions also have been successfully carried out with asymmetric variants, thus contributing to the chiral pool. The user friendly "trio" enables easy generation of these versatile sulfur analogues and the reaction condition employed depict an economic outline.